Assessing the effects of the environment on consumers' evaluations for wine - Gioacchino Pappalardo; Gaetano Chinnici; Roberta Selvaggi; Biagio Pecorino (Wine Economics and Policy, 2020)
In the wine sector, experiential marketing is becoming increasingly important since the success of a wine hinges on "experiential" attributes that include hedonic and symbolic values associated with emotions. An aspect not yet fully explored in the scientific literature concerns the extent to which emotions aroused by the environment where wine is consumed are able to influence consumers' evaluation of wine. To this end, we conducted an economic experiment in Italy in the territory of Mt Etna, Sicily and through a non-hypothetical experimental auction we assessed the effects of 10 emotions related to the environment of Mt Etna on consumers' Willingness to Pay (WTP) for Etna wine. The results of this study show that the values of consumers' WTP for wine are affected by emotions aroused by the experiential environment of Mt Etna.
Keywords: 330; wine; experiential consumption; experimental auction